Carpal tunnel syndrome. Clinical and neurophysiological correlation - PORTILLO, ROBERTO (2004)
Objective: To determine clinical and neurophysiological characteristics of carpal tunnel syndrome Material and Methods: We made a clinical-electrophysiological correlation of 381 hands pertaining to 308 patients, during four years in patients of the Neurophisiological service, Guillermo Almenara Irigoyen National Hospital (electromyography of wrist thumb short abductor, nervous conduction velocity: median nerve motor and sensitivity, nervous conduction to carpal level). Results: About 81% of patients were between 30 an 60 year-old, 53% were female, 50% had manual occupation. Symptoms and signs were parestesia, pain and Tinel syndrome. Electromyography was considered normal in 80% of cases; 50% of patients showed over 6 msec latency or inexcitability. Nervous conduction velocity of carpal level was 12,5 m/sec average. Sensitive distal latency was severely compromised in 40% of patients. Conclusions: Motor and sensitive nervous conduction velocity are diagnosis methods of carpal tunnel syndrome; clinical-electrophysiological correlation evidenced lesions of three degrees: slight, mild and severe; 85% had significant lesion in the right hand, related to occupational activity.